AN EFFECTIVE PRE-TEACHING ACTIVITY TO BUILD STUDENTâS ORAL COMMUNICATION SKILL - Nurhasanah, Amalia (Reflective, 2013)
Oral communication skill is the ability to receive and process the information (listening) and then respond and produce language (speaking) for which the messages delivered across and communication can run successfully. To most Indonesian students, speaking and listening English as can be challenging. Many factors influence how well someone can communicate orally in English, for instance: physical tools (ear and mouth), vocabulary mastery, grammatical knowledge, spoken discourse, and so forth. Therefore, I propose one technique namely âThree-Minute Descriptive Speechâ which is executed during preteaching session to the students of The State Institute for Islamic Studies Sulthan Thaha Saifuddin (IAIN STS) Jambi. The qualitative data taken from twenty-seven students through openquestionnaires were analyzed. I found that the application of the technique gave benefits to the students, such as raising confidence, increasing motivation, and enhancing their oral communication skill.Keywords: Descriptive Speech, Speaking Skill, Oral Communication, Feedback